Long non-coding RNA GASL1 inhibits proliferation and invasion of osteosarcoma cells via modulation of the PI3K/Akt pathway - Feng Gao; Feng Xu (Archives of Medical Science, 2019)
Introduction Studies have shown long non-coding RNAs to be involved in a wide array of cancer-related processes. This study analyzed the role of LncRNA GAL1 in osteosarcoma cancer proliferation, migration and invasion of cancer cells.